Effects of Substituting Soybean Meal with Fermented Rubber Leaves and Seeds (Hevea brasilliensis) on Egg Production and Egg Quality in Native Laying Hens - Syahruddin , Erman; Herawaty, R.; Azhar, (International Journal of Poultry Science, 2016)
This study aims to determine the levels of fermented rubber leaves and seeds that can be used to substitute 100% of the soybean meal in native laying hen rations without adverse effects on laying hen production. Two hundred and forty laying hens aged 20 weeks were used in this experiment. The completely randomized design assigned six treatments to replace 0, 20, 40, 60, 80 or 100% of soybean meal with fermented rubber leaves and seeds in four replicate experiments. The variables measured were feed intake, feed conversion and income over feed cost (gross profit) as well as variables related to egg production (hen day production and egg weight) and egg quality (the thickness of eggshells and the yolk color index). Data were analyzed statistically using ANOVAs and if the results showed significance, Duncan's Test (DMRT) was used. The results showed that the performance of laying hens was not affected significantly by substituting soybean meal with fermented rubber leaves and seeds. Feed intake, feed conversion and egg production were not influenced either. In summary, fermented rubber leaves and seeds can substitute for 100% of the soybean meal in the rations of laying hens.